Developing a green and edible film from Cassia gum: The effects of glycerol and sorbitol. (20th February 2018) - Cao, Lele; Liu, Wenbo; Wang, Lijuan
Abstract: The feasibility of preparing a novel edible film based on cassia gum (CG) was studied. The mechanical, barrier, optical, and thermal properties as well as the contact angle were determined to evaluate the effect of glycerol (G), sorbitol (S) in various concentrations on the CG films. The rheology properties of the film-forming solutions were also analyzed. The Fourier transform infrared spectroscopy (FTIR) analysis showed that hydrogen bonds formed between the G or S and CG molecules. The viscosity tests revealed the film-forming solutions had a shear-thinning behavior and the dynamic measurements confirmed that the glycerol-added CG (CG-G) and sorbitol-added CG (CG-S) solutions exhibited classical gel properties. The CG-G films had higher elongation at break (EB) but lower water vapor permeability (WVP) and oxygen permeability (OP) than CG-S ones. Therefore, tensile strength (TS) increased with increasing G (except for 50%) and S concentrations. The TS of CG-G and CG-S films increased from 11.02 ± 0.47 to 18.53 ± 0.40 MPa, and from 12.69 ± 0.59 to 18.20 ± 0.76 MPa, respectively; the corresponding EB increased from 22.27 ± 0.47 to 38.00 ± 0.59% and from 7.90 ± 0.41 (CG-30S) to 25.33 ± 0.90%, indicating that G or S played as not only a plasticizer but also a cross-linker. An increase in G and S concentrations also made the films more opaque and improved their thermal stability. CG is a promising material for the production of edible packaging films. Graphical abstract: Image Highlights: A novel, environmentally friendly and edible film was prepared from Cassia gum (CG). Tensile strength of CG films increased after glycerol and sorbitol were added. CG films presented good mechanical properties and low water vapor permeability. CG films were reinforced by glycerol and sorbitol at concentrations of 45% and 50%, respectively.